KARAMAH MENURUT SHAYKH DR. HJ. JAHID HJ. SIDEK - Ahmad Najaa Mochtar (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
Karamah is always associated with pekara extraordinary or magic pekara. In fact, this study will discuss matters related to karamah, including istidraj (magic). The discussion focused on the definition of karamah and other terms related to the understanding of the Muslim community in Malaysia in particular. In addition, this study presents the phenomenon of karamah in Islamic societies in Malaysia, and so on, an analysis of the phenomenon of karamah in Islamic society according to Dr. Shaykh's perspective. Jahid Hj. Sidek. This study method is based on library studies and field studies. The formulation of the acquisition states that karamah is a gift from Allah SWT without one's efforts to obtain it, while istidraj, which is an extraordinary case, has the element of help from the genie and the devil. Generally, some Islamic societies cannot differentiate between karamah and istidraj as explained by Islamic law.